2019
DOI: 10.1088/1755-1315/372/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight and Body Measurements of Purebred and Crossbred Belgian Blue Calves

Abstract: The Belgian Blue (BB) is a breed of cattle characterized by double muscling. Introduction of Belgian Blue cattle to Indonesian is to increase beef production. A preliminary study was done to compare birth weight and body measurements of purebred BB calves to F1 BB x Friesian Holstein (FH) calves. A total of 10 purebred BB calves and 20 F-1 BB x FH calves were used in this study. Results showed that birth weight and chest girth were significantly affected by genotype of calves (P<0.05). The purebreds had hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The higher performance of purebred BB cattle than the crossed cattle at birth age in this study was similar to the result reported by Praharani et al (2019). In their research, the purebred BB cattle had a higher body weight and chest girth than the F1 BB x FH reared at the Dairy Goat Unit of the Indonesian Institute for Animal Production (IRIAP).…”
Section: Growth Performance Of Bb Cattle and Its Crossbred Offspringsupporting
confidence: 90%
See 1 more Smart Citation
“…The higher performance of purebred BB cattle than the crossed cattle at birth age in this study was similar to the result reported by Praharani et al (2019). In their research, the purebred BB cattle had a higher body weight and chest girth than the F1 BB x FH reared at the Dairy Goat Unit of the Indonesian Institute for Animal Production (IRIAP).…”
Section: Growth Performance Of Bb Cattle and Its Crossbred Offspringsupporting
confidence: 90%
“…Livestock growth performance is reflected in body weight and size (Chalid et al, 2023;Praharani et al, 2019). Body measurements are important to characterize the breed of cattle (Hailu and Getu, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Fattening characteristics (final weight, slaughter weight, average daily gain) were highest in the group of medium LBW (Table 1); however, results were not significant. According to Praharani et al (2019) birth weight of calves is an important contributory factor for improving growth performance.…”
Section: Resultsmentioning
confidence: 99%
“…Tindakan operasi caesar diperlukan untuk mengatasi distosia. Distosia disebabkan karena pedet memiliki ukuran yang besar atau bobot lahir tinggi (Praharani, 2019).…”
Section: Pendahuluanunclassified